Biochemical, Physiological and Technological Properties of Lactic Acid Bacteria Isolated and Characterized from Hard and Soft Wheat: LACTIC ACID BACTERIA ISOLATED AND CHARACTERIZED FROM WHEAT - Guetarni, Hassina (Annals of Arid Zone, 2024)
Population of lactic acid bacteria (LAB) adhering on three samples of wheat grain, viz. Algerian durum wheat, Canadian durum wheat and French soft wheat and a sample of bread flour, collected from the Semoulerie Industrielle de la Mitidja was cultured and identified to determine their diversity. Fifty four lactic acid bacteria were isolated. They belonged to 20 species of eight genera (Pediococcus, Enterococcus, Lactobacillus, Lactococcus, Weissella, Streptococcus, Leuconostoc and Aerococcus). The Enterococcus genus represented 42% of the isolated strains, followed by Streptococcus (19%), Lactococcus (11%), Lactobacillus (9%) and Pediococcus (9%), Leuconostoc (4%) and Weissella (4%) and the Aerococcus (2%). Nineteen biochemical and physiological parameters of LAB population were estimated along with four technological properties were studied. Oxidase, mannose, urease, nitrate reductase and haemolysis were negative for all species. All the 54 strains tested showed acidifying capacity, proteolytic nature and lipase activity. All except Enterococcus acidominimus B8 and B14, Streptococcus thermophilus B13, both strains of Lactococcus lactis ssp. cremoris, Lactococcus lactis ssp. lactis, Leuconostoc mesenteroides subsp. mesenteroides did not possess lacithinase activity. Leuconoctoc mesenteroides subsp. mesenteroides was the most efficient acid producing strain. It was closely followed by Lactobacillus fermentum and Leuconostoc mesenteroides subsp. dectranicum. Close similarity in their biochemical and physiological characters showed that efficiency of any new species for industrial and household suitability for fermentation can be predicted on the basis of similarity in their characters with Leuconoctoc mesenteroides subsp. mesenteroides.